Analisis Uji Komparasi Customer Satisfaction Survey Dalam Penggunaan Google Cloud Platform (GCP) Menggunakan Metode Pieces Dan System Usability Scale - Eri Riana; Meiva Eka Sri Sulistyawati; Adianta Sebayang (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2023)
Cloud Computing technology makes a technology that is most often applied later in the future. Currently, cloud computing technology provides many types of services, including cost management services, data analysis, big data, storage, machine learning, big data, AI, IoT, and application development. Cloud computing technology has made a service and solution, both to increase reliability, reduce computing costs, to provide a great opportunity for the ICT industry to benefit more from cloud computing technology. Customer satisfaction is a level of feeling from someone after being able to compare the performance or results that are felt and obtained compared to their expectations or can be interpreted as a response to customer feedback in using cloud computing technology and an assessment of the good and bad of cloud computing technology which can be used as a reference or a benchmark for cloud computing developers to improve the performance of cloud computing technology that has been built. The level of customer satisfaction can be found using many model methods. In this study the level of satisfaction will be analyzed using the PIECES method and the System Usability Scale. In this study, researchers used two model methods and then carried out a comparative test of these methods. The PIECES variables are Performance, Information and data, Economics, Control and security, Efficiency and Service. The results of the study obtained an average value for each domain, namely the Performance domain with a value of 4.40 (Very Satisfied), Information and data with a value of 4.30 (Very Satisfied), Economics with a value of 4.33 (Very Satisfied), Control and security with a value of 4.28 (Very Satisfied), Efficiency with a value of 4.96 (Very Satisfied) and Service with a value of 4.00 (Satisfied). The recapitulation results for the average value for the entire domain level with a value of 4.37 (Very Satisfied). In the System Usability Scale method, a score of 82.08 is entered in the Acceptable category and grade A. With the comparative test results of the two methods, the satisfaction level of Google Cloud Platform customers is stated to be very satisfied and very good by the customers.